The Role of Interpersonal Communication for the Diffusion of the Elsimil Application among Family Assistance Teams - Jesyka Mutiara Yuda; Nanang Trenggono; Nina Yudha Aryanti; Abdul Firman Ashaf; Ibrahim Besar (KOMUNIKA, 2025)
This study explores the role of interpersonal communication in disseminating and introducing the Elektronik Siap Nikah dan Hamil (Elsimil) application to Family Assistance Teams (TPK). This study, a novel piece of research, comprehensively analyzes interpersonal communication in the diffusion of Elsimil, a digital innovation in public health for accelerating stunting reduction, initiated by BKKBN. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document analysis involving 10 informants over three months. The findings indicate that interpersonal communication plays a crucial role throughout all stages of innovation diffusion: knowledge (introducing and providing initial information), persuasion (building interest and positive attitudes), decision (encouraging adoption), implementation (guiding practical use and addressing challenges), and confirmation (ensuring sustainability). Family planning counselors serve as early adopters and opinion leaders, facilitating application adoption and bridging technical and psychological barriers faced by TPK cadres. As the first group trained on Elsimil, counselors become the primary point of reference for hesitant cadres who lack sufficient understanding. Theoretically, this study enriches Rogers' Diffusion of Innovations Theory for the implementation of digital technology in public health services, specifically in stunting prevention programs. It demonstrates how interpersonal communication and opinion leadership accelerate the adoption of innovation in community-based health interventions. Practically, the findings provide valuable insights for BKKBN and program implementers to enhance family planning counselors' digital literacy and interpersonal communication competencies, ultimately strengthening the effectiveness of stunting prevention initiatives through improved cadre support systems.